The Impact of Oil Palm Expansion on Environmental Change: Putting Conservation Research in Context - Turner, Edgar C.; Snaddon, Jake L.; Ewers, Robert M.; Fayle, Tom M.; Foster, William A. (IntechOpen, 2011)
None